2011
DOI: 10.1002/cne.22650
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin‐expressing olivocochlear neurons exhibit tonotopic and developmental changes in the auditory brainstem and in the innervation of the cochlea

Abstract: The mammalian cochlea is under direct control of two groups of cholinergic auditory brainstem neurons, the medial and the lateral olivocochlear neurons. The former modulate the electromechanical amplification in outer hair cells and the latter the transduction of inner hair cells to auditory nerve fibers. The lateral olivocochlear neurons express not only acetylcholine but a variety of co-transmitters including urocortin, which is known to regulate homeostatic responses related to stress; it may also be relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…Lateral olivocochlear (LOC) neurons, which are intermingled with principal cells in the LSO in gerbils (Kaiser et al 2011) and mice (Sterenborg et al 2010), have capacitance of only 50% compared with principal neurons (in our experiments, around 10 pF) and display a depolarized resting membrane potential, a delay-type firing pattern, and specific inward and outward current properties (Sterenborg et al 2010). These criteria were used to exclude LOC neurons in the current-clamp mode.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Lateral olivocochlear (LOC) neurons, which are intermingled with principal cells in the LSO in gerbils (Kaiser et al 2011) and mice (Sterenborg et al 2010), have capacitance of only 50% compared with principal neurons (in our experiments, around 10 pF) and display a depolarized resting membrane potential, a delay-type firing pattern, and specific inward and outward current properties (Sterenborg et al 2010). These criteria were used to exclude LOC neurons in the current-clamp mode.…”
Section: Methodsmentioning
confidence: 96%
“…Comparative posthearing development of inhibitory inputs to the lateral superior olive in gerbils and mice. J Neurophysiol 106: 1443-1453, 2011. First published June 22, 2011 doi:10.1152/jn.01087.2010.-Interaural intensity differences are analyzed in neurons of the lateral superior olive (LSO) by integration of an inhibitory input from the medial nucleus of the trapezoid body (MNTB), activated by sound from the contralateral ear, with an excitatory input from the ipsilateral cochlear nucleus.…”
mentioning
confidence: 99%
“…For choline acetyltransferase (ChAT), a polyclonal antibody (AB144P; Millipore) was used that recognizes a single expected band at ∼70 kDa (Western Blot analysis; Kaiser et al 2011). Antibodies directed against MAP2 are shown to detect MAP2a and -b variants at ∼280 kDa and -c variant at 70 kDa in Western blot analysis (data sheet and personal communication from Neuromics).…”
Section: Methodsmentioning
confidence: 99%
“…The lateral efferent fibers originate from cells in the lateral superior olive that have been shown to express Ucn1 (Kaiser et al, 2011). Assessment of auditory function in Ucn1 null mice revealed that Ucn1 plays an important role in sound processing.…”
Section: Urocortin Is Expressed In the Cochleamentioning
confidence: 99%